Influence of Dietary Black Pepper Meal Supplementation on the Haemato-Serological Profile of West African Dwarf Goats - O. B. Omotoso; Kehinde Oluwatomisin Ogundeyibi; Teniola Oso (Turkish Journal of Agriculture: Food Science and Technology)
Phytogenic feed additives, such as black pepper meal (BPM), show promise for improving animal health and productivity. However, its application in ruminant nutrition remains underexplored. Thus, a 56-day study was conducted to assess the effect of BPM supplementation on nutrient intake, haematological, and serum biochemical indices in West African Dwarf (WAD) goats. A basal diet was formulated and divided into four equal portions. Each portion was supplemented with BPM at 0 (control), 250, 500, and 750 mg and designated as Diet A, B, C and D, respectively. Twenty WAD goats (average liveweight 5.00±0.23 kg) were assigned to the four dietary treatments. Blood samples were collected for haematological while serum harvested were used for serum biochemical analyses. Dietary DM, CP and NFE slightly decreased with increased BPM supplementation. DM intake significantly increased from 312.28±12.09 g/day (Diet A) to 316.88±14.74 g/day (Diet D) (p<0.05).  Crude protein and fiber intake increased slightly. It is noteworthy that supplementation of BPM did not significantly influence the observed haematological parameters (p>0.05). Serum biochemical indices did not follow a particular trend. However, goats fed Diet B had significantly higher total protein (72.00±4.83 g/L) and globulin (34.00±3.09 g/L) compared to other treatments (p<0.05). The study revealed that use of BPM supplementation in goats’ diets may not be essential, however, supplementation up to 750 mg/100 kg (Diet D) may support intake and thus, enhance immune functions, positioning BPM as additive to improve animal’ health without adverse effect.